Crescimento e produtividade da mamoneira sob adubação verde,associada à adubação orgânica - Juliano de Castro Maia (2012)
Mamoneira due to the versatility of the use of its oil, come arousing the interest of producers and entrepreneurs from all the country.It is a rustic culture, adapted to the different conditions of climate and soil of Brazil.Several studies have shown that this culture responds well to soil fertilization and irrigation.The present research was developed with the objective to evaluate the productivity of mamoneira grown under green manure, associated with organic manure.The experiment was conducted at the FazendaRiacho, municipality of Claro dos Poções - MG, being the experiment area irrigated.The experimental design used was the randomized blocks with treatments arranged in a factorial design, with 2 additional treatments 2 x 5 + 2, being the first factor the use or not of green manure, the second factor 5 doses of chicken manure, equivalent to 0, 50, 100, 150 and 200% of recommended dose of nitrogen for the crop and 2 additional treatments, compounds of recommended chemical fertilization and spontaneous vegetation as cover plant.We evaluated growth and productivity parameters of mamoneira.The obtained results demonstrate the positive effect of green manure about the growth characteristics evaluated and about the productivity of plants, which is equivalent to that obtained with chemical manure and with organic manure recommended.